Distribusi radionuklida alam dalam sampel lingkungan tanah, air dan tanaman sekitar PLTU Rembang - Aditya Yoga Syah Putra; Dwi P. Sasongko; Zaenal Arifin; Sukirno Sukirno (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Research of the natural radionuclide distribution of soil, water and plant samples around Rembang Coal Fired Power Plant (CFPP) has been done with the purpose of the study is to know the activity concentration of natural radionuclide, the pattern of distribution of environtment radioactivity around Rembang CFPP with soil, water and plant samples and compare the activity concentration of natural radionuclide around Rembang CFPP with Environmental Radioactivity Limit Values (ERLV) which is listed on the Perka Bapeten No 16 of 2013 about Safety Radiation in Storage of Technologically Enhanched Naturally Occuring Radioactivity Material. Sample analysis method using gamma spectrometry with HPGe detector and Maestro 2 software is based on SNI 1070.3-2009. The calculated concentration of natural radionuclide activity 226Ra, 228Ra, 232Th dan 40K in soil sample is (8.17×10-3 ± 2.33×10-4; 9.99×10-3 ± 1.69×10-4; 7.84×10-3 ± 2.78×10-4; 4.46×10-2 ± 6.78×10-4) Bq/g. Water sample (3.07×10-3 ± 4.05×10-4; 3.59×10-3 ± 3.22×10-4; 6.59×10-4 ± 5.59×10-5; 2.82×10-2 ± 1.93×10-3) Bq/L. Plant sample (1.69×10-3 ± 9.06×10-5; 7.56×10-4 ± 5.04×10-5; 4.13×10-4 ± 3.03×10-5; 1.17×10-2 ± 7.52×10-4) Bq/g. The distribution pattern of the concentration of natural radionuclide activity that is formed that is in the soil sample has the distribution pattern of the distance from CFPP Rembang the bigger concentration activity. Furthermore, in water and plant samples the distribution pattern tends to lead to a location close to the CFPP that has a bigger concentration of activity. Comparison the concentration of natural radionuclide activity with Environmental Radioactivity Limit Values (ERLV) it was found that the overall concentration of natural radionuclide activity in soil, water or plant samples at each sampling site still did not exceed the Environmental Boundary Limit Radioactivity (ERLV) that defined by Perka Bapeten No 16 of 2013 about Safety Radiation in Storage of Technologically Enhanched Naturally Occuring Radioactivity Material.Keywords: Natural radionuclide, environment sample, Rembang CFPP, gamma spectrometry, radioactivity, distribution.